Pengelolaan Bahasa Untuk Pembelajaran Di Indonesia - Zuniar Kamaluddin Mabruri (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2021)
This study aims to understand language management for learning in Indonesia. The research method used is a qualitative method with the type of literature study. The results show that the State of Indonesia has carried out language management in relation to the recognition of existing languages and is regulating for the government in the context of the state and nation so that there is a triangular relationship between language and the state which is regulated by the government for the benefit of the nation. If the state has guaranteed the existence of a language as a whole, then a number of policies will emerge to guarantee the rights and obligations of each in managing the existing language. Policies are formulated in the form of rules known as regulations, to serve as joint guidelines between the government and speakers of existing languages.